Food Safety in Developing Countries: Common Foodborne and Waterborne Illnesses, Regulations, Organizational Structure, and Challenges of Food Safety in the Context of Nepal - Deepak Subedi; Madhav Paudel; Sandesh Poudel; Niranjan Koirala (Food Frontiers)
ABSTRACT Food safety presents a global challenge, contributing to 600 million cases of foodborne diseases and 420,000 fatalities annually worldwide. In developing countries, such as Nepal, addressing food safety is particularly intricate and arduous because of the prevalent issues of food insecurity, poverty, illiteracy, and regulatory hurdles. The objectives of this comprehensive review are to evaluate the prevalent foodborne and waterborne illnesses, examine the existing regulations and institutional frameworks, and identify the challenges associated with food safety in Nepal. Additionally, this review aims to propose strategies to enhance food safety measures in the country. An electronic search was conducted using relevant keywords to include articles and literature pertinent to the topic. Common foodborne illnesses in Nepal include cholera, typhoid fever, hepatitis, worm infections, and poisoning from mushrooms, heavy metals, and pesticides. While existing rules, regulations, and government infrastructure exist, they often face limitations in effectively addressing these multifaceted challenges. Food safety in developing countries, such as Nepal, faces several challenges, including inadequate regulatory frameworks, limited surveillance and monitoring, rural–urban disparities, and high incidences of foodborne illness. Additional issues stem from weak law enforcement, poor food safety practices, limited infrastructure, informal sector challenges, cross‐border trade, limited access to clean water, and the impacts of climate change. A multisectoral One Health approach involving collaboration among government agencies, food industry stakeholders, consumers, and civil society organizations is imperative to enhance food safety in developing countries such as Nepal.